Schwarzian Derivative Treatment of the Quantum Second-Order Supersymmetry Anomaly, and Coupling-Constant Metamorphosis - Pliouchtchai, M (Academic Press, 2017)
A canonical quantization scheme applied to a classical supersymmetric system with quadratic in momentum supercharges gives rise to a quantum anomaly problem described by a specific term to be quadratic in Planck constant. We reveal a close relationship between the anomaly and the Schwarzian derivative, and specify a quantization prescription which generates the anomaly-free supersymmetric quantum system with second order supercharges. We also discuss the phenomenon of a coupling-constant metamorphosis that associates quantum systems with the first-order supersymmetry to the systems with the second-order supercharges. © 2016 Elsevier Inc.